Adhesion of volatile propofol to breathing circuit tubing. (21st August 2017) - Lorenz, Dominik; Maurer, Felix; Trautner, Katharina; Fink, Tobias; Hüppe, Tobias; Sessler, Daniel I; Baumbach, Jörg Ingo; Volk, Thomas; Kreuer, Sascha
Abstract: Propofol in exhaled breath can be measured and may provide a real-time estimate of plasma concentration. However, propofol is absorbed in plastic tubing, thus estimates may fail to reflect lung/blood concentration if expired gas is not extracted directly from the endotracheal tube. We evaluated exhaled propofol in five ventilated ICU patients who were sedated with propofol. Exhaled propofol was measured once per minute using ion mobility spectrometry. Exhaled air was sampled directly from the endotracheal tube and at the ventilator end of the expiratory side of the anesthetic circuit. The circuit was disconnected from the patient and propofol was washed out with a separate clean ventilator. Propofol molecules, which discharged from the expiratory portion of the breathing circuit, were measured for up to 60 h. We also determined whether propofol passes through the plastic of breathing circuits. A total of 984 data pairs (presented as median values, with 95% confidence interval), consisting of both concentrations were collected. The concentration of propofol sampled near the patient was always substantially higher, at 10.4 [10.25–10.55] versus 5.73 [5.66–5.88] ppb ( p < 0.001). The reduction in concentration over the breathing circuit tubing was 4.58 [4.48–4.68] ppb, 3.46 [3.21–3.73] in the first hour, 4.05 [3.77–4.34] in the second hour, and 4.01 [3.36–4.40] in the third hour. Out-gassing propofol from the breathing circuit remained at 2.8 ppb after 60 h of washing out. Diffusion through the plastic was not observed. Volatile propofol binds or adsorbs to the plastic of a breathing circuit with saturation kinetics. The bond is reversible so propofol can be washed out from the plastic. Our data confirm earlier findings that accurate measurements of volatile propofol require exhaled air to be sampled as close as possible to the patient.